TINJAUAN YURIDIS TERHADAP PERIKATAN DALAM METODE PEMBAYARAN DIGITAL PENYEDIA JASA TRANSPORTASI ONLINE BAGI PENGGUNA JASA - Shenti Agustini (Journal of Judicial Review, 2019)
Globalization has basically been implemented in cyberspace, which connects all digital societies or those who often use the internet in their daily activities. Transportation development also includes the method of ordering and payment of transactions for transportation services. In the past, transportation service users ordered via telephone and then paid in cash. In its current development, there are transportation that can be ordered and paid for in a darling (online) system that connects passengers with car drivers through a mobile application In order to answer the problems in this study, the author uses a type of normative research supported by primary data obtained by the author from interviews with various sources. According to observations made by the author, the provider of transportation services with a digital payment system under the auspices of the limited liability company Dompet Anak Bangsa is not fulfilling the terms and conditions to secure the balance (money) owned by users of transportation services with the digital payment system. This situation has a correlation with the results of the author's interview discussed above. Other parties who do not have the right to access the digital payment system and access the balance held by users of transportation services with digital payment systems. Therefore, digital providers of transportation services should also be responsible for reducing the balance of digital payment systems owned by service users because of anything. The intended liability due to the reduction in balance is very detrimental to the service user and the balance is reduced in the digital payment system provided by the service provider. Although this problem is also a criminal offense that can be reported to the police because it is related to cyber crime.